2019
DOI: 10.1109/tuffc.2019.2926211
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film PZT-Based PMUT Arrays for Deterministic Particle Manipulation

Abstract: Lead zirconate titanate (PZT) based piezoelectric micromachined ultrasonic transducers (PMUTs) for particle manipulation applications were designed, fabricated, characterized and tested. The PMUTs had a diaphragm diameter of 60 µm, a resonant frequency of ~ 8 MHz and an operational bandwidth of 62.5%. Acoustic pressure output in water was 9.5 kPa at 7.5 mm distance from a PMUT element excited with a unipolar waveform at 5 Vpp. The element consisted of 20 diaphragms connected electrically in parallel. Particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The bottom electrode was deposited by sputtering 30 nm of Ti, annealing it at 700 °C for 15 min with 10 sccm of oxygen flow, and then sputtering 100 nm of Pt at a substrate temperature of 500 °C [ 14 ]. To facilitate orientation of the piezoelectric film, a PZT seed layer (Mitsubishi Materials Corporation, Hyogo, Japan) was spun, pyrolyzed, and crystallized, as described elsewhere [ 10 , 15 , 16 , 17 ]. For the MPB composition, 14 mol% lead excess Pb(Zr 0.52 Ti 0.48 )O 3 solution doped with 2% Nb (Mitsubishi Materials Corporation, Hyogo, Japan) was spun on at 2750 RPM for 45 s. The film was pyrolyzed at 100 °C for 1 min and 300 °C for 4 min, followed by crystallization in a lead-rich rapid thermal annealer for 1 min at 700 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bottom electrode was deposited by sputtering 30 nm of Ti, annealing it at 700 °C for 15 min with 10 sccm of oxygen flow, and then sputtering 100 nm of Pt at a substrate temperature of 500 °C [ 14 ]. To facilitate orientation of the piezoelectric film, a PZT seed layer (Mitsubishi Materials Corporation, Hyogo, Japan) was spun, pyrolyzed, and crystallized, as described elsewhere [ 10 , 15 , 16 , 17 ]. For the MPB composition, 14 mol% lead excess Pb(Zr 0.52 Ti 0.48 )O 3 solution doped with 2% Nb (Mitsubishi Materials Corporation, Hyogo, Japan) was spun on at 2750 RPM for 45 s. The film was pyrolyzed at 100 °C for 1 min and 300 °C for 4 min, followed by crystallization in a lead-rich rapid thermal annealer for 1 min at 700 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The design, fabrication process, and characterization for circular 6–8 MHz PMUTs are described elsewhere [ 10 , 17 ]. The PMUTs were wire-bonded to a pin grid array (PGA) or a circuit board and coated with 2 µm of parylene for waterproofing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small size and low driving voltage make it easy to integrate into wearable devices and low acoustic impedance mismatching makes higher frequency applications (>250 kHz) possible, which leads to better resolutions. Several applications of pMUT, such as levitation, photoacoustic imaging, and particle manipulation, have been developed with different fabrication approaches and achieved promising results [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nakazawa et al [ 5 ] fabricated eight-element, 200 µm pitch and 32-element, 20-µm pitch, 1D arrays based on a polyurea film, and experimentally measured the resonance frequencies at 30 MHz, 65 MHz, and 100 MHz. Cheng et al [ 6 ] reported a 2D PMUT array consisting of 20 diaphragms, with each diaphragm having 60 µm diameter, and showed its resonance frequency at 8 MHz with 62.5% bandwidth. 9.5 kPa of acoustic pressure was measured by a hydrophone (HGL-0085, Onda, Inc,.)…”
Section: Introductionmentioning
confidence: 99%